Development of the method and program model of the static analyzer of harmful files - Gavrylenko, Svitlana; Saenko, Dmitriy (НТУ "ХПІ", 2017)
The subject of research in this article is the methods of analyzing malicious software. The goal is to improve the secure functioning of computer systems (CS) and protect them from the effects of computer viruses. Research target: the research of modern means of software antivirus protection; analysis of the methods of creating a file signature; the development of a software model for static file detection, based on the analysis of the PE structure; the generation of tables of features that are inherent to families of viruses such as Worms, Backdor, Trojan; the obtainment binary signatures of malicious and secure software. The methods used are: analysis of the code in a Hex file, file hashing algorithms. The following results are obtained. The PE-structure of the file has been analyzed; sections have been selected for further analysis. A software model of static file detection has been developed and the analysis of secure and malicious files has been performed. Features in the form of strings and API functions have been selected; a bitmask has been formed for further file analysis. 3500 files of malicious and safe software has been scanned, their analysis has been performed. Signatures of each malicious file have been encoded and stored in the signature database. Using the developed software model, a study has been made of the possibility of detecting modifications to malicious software. Conclusions. A method and software model of static detection of malicious files has been developed, which allow automatic obtainment of a set of file features and draw a conclusion about the severity of the file.

Предметом дослідження в даній статті є методи аналізу шкідливого програмного забезпечення. Мета статті полягає в підвищенні безпеки функціонування комп'ютерних систем (КС) і захисту їх від впливу комп'ютерних вірусів. Завдання: дослідження сучасних засобів антивірусного захисту програмного забезпечення; аналіз методів формування сигнатури файлів; розробка програмної моделі статичного детектування файлів, що базується на аналізі PE-структури; формування таблиць ознак, притаманних родин вірусів типу Worms, Backdor, Trojan; отримання довічних сигнатур шкідливого і безпечного програмного забезпечення. Використовуваними методами є: аналіз коду в Hex-файлі, алгоритми хешування файлів. Отримані наступні результати. Проаналізовано РЕ-структуру файлу, обрані секції для подальшого аналізу. Розроблена програмна модель статичного детектування файлів і виконано аналіз безпечних і шкідливих файлів. Обрані ознаки у вигляді рядків і API функцій, сформована бітова маска для подальшого аналізу файлів. Виконано сканування 3500 файлів шкідливого і безпечного програмного забезпечення, проведено їх аналіз. Сигнатури кожного шкідливого файлу закодовані і збережені в базі сигнатур, За допомогою розробленої програмної моделі виконано дослідження можливості виявлення модифікацій шкідливого програмного забезпечення. Висновок. Розроблено метод і програмну модель статичного детектування шкідливих файлів, що дозволяє отримати набір ознак файлу в автоматичному режимі і зробити висновок про шкідливість файлу.
Розробка методу і програмної моделі статичного аналізатора шкідливих файлів
Keywords: malicious software; signature; Python; portable execute; malicious application; API functions; harmful files; шкідливе програмне забезпечення; сигнатура; портативний запуск; шкідливий додаток; API-функції; шкідливі файли